2021
DOI: 10.1101/2021.08.10.455644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibodies control metabolism by regulating insulin homeostasis

Abstract: Homeostasis of metabolism by hormone production is crucial to maintain physiological integrity and disbalance can cause severe metabolic disorders such as diabetes mellitus. Here, we show that antibodies recognizing insulin are key regulators of blood glucose and metabolism controlling insulin concentrations. In fact, antibody-deficient mice and immunodeficiency patients show sub-physiological blood glucose, which becomes normal after total IgG injection. We show that insulin-specific IgG antibodies found in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…In full agreement, our recent work showed that blood glucose levels are tightly regulated by insulin-specific autoantibodies of the IgM and IgG class (17,18). In particular, we demonstrated that insulin-specific IgG neutralizes circulating insulin in wild-type (WT) mice, while PR-IgM autoantibodies with high specificity and affinity for insulin, generated in the course of secondary immune responses, play a protective role on circulating insulin by preventing IgG-induced insulin degradation.…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…In full agreement, our recent work showed that blood glucose levels are tightly regulated by insulin-specific autoantibodies of the IgM and IgG class (17,18). In particular, we demonstrated that insulin-specific IgG neutralizes circulating insulin in wild-type (WT) mice, while PR-IgM autoantibodies with high specificity and affinity for insulin, generated in the course of secondary immune responses, play a protective role on circulating insulin by preventing IgG-induced insulin degradation.…”
Section: Introductionsupporting
confidence: 77%
“…To confirm our hypothesis that IgM affinity and specificity determines the outcome of the interaction with the recognized cognate antigen, we used recombinant anti-insulin antibodies as model. In our previous study, we cloned a monoclonal antiinsulin antibody and studied its effect on insulin function when expressed as IgG or IgM isotype (18). This monoclonal antibody has high affinity (K D 10 -9 ) to its target autoantigen and neutralized insulin when expressed as IgG, while expression as IgM protected insulin from IgG-mediated neutralization in vivo (18).…”
Section: Recombinant Low Affinity Anti-insulin Igm Neutralizes Insuli...mentioning
confidence: 99%
See 3 more Smart Citations